Hasil dari :
[tex] \sqrt[5]{32} + \sqrt[4]{81} - \sqrt[3]{8} + \sqrt[2]{9} - 3 \: \: [/tex]
*****
[tex] \sqrt[5]{32} + \sqrt[4]{81} - \sqrt[3]{8} + \sqrt[2]{9} - 3 \: \: [/tex]
*****
>> Bentuk Akar
--
[tex] \sf\sqrt[5]{32} + \sqrt[4]{81} - \sqrt[3]{8} + \sqrt[2]{9} - 3 \: [/tex]
[tex] \sf = {32}^{ \frac{1}{5} } + {81}^{ \frac{1}{4} } - {8}^{ \frac{1}{3} } + 3 - 3[/tex]
[tex] \sf = {( {2}^{5}) }^{ \frac{1}{5} } + {( {3}^{4}) }^{ \frac{1}{4} } - {( {2}^{3} )}^{ \frac{1}{3} } [/tex]
= 2 + 3 - 2
= 5 - 2
= 3
Penjelasan dengan langkah-langkah:
[tex] = \sqrt[5]{32} + \sqrt[4]{81} - \sqrt[3]{8} + \sqrt[2]{9} - 3[/tex]
[tex] = \sqrt[ \cancel5]{ {2}^{ \cancel5} } + \sqrt[ \cancel4]{ {3}^{ \cancel4} } - \sqrt[ \cancel3]{ {2}^{ \cancel3} } + \sqrt[ \cancel2]{ {3}^{ \cancel2} } - 3[/tex]
[tex] = 2 + 3 - 2 + 3 - 3[/tex]
[tex] = 5 - 2 + 3 - 3[/tex]
[tex] = 3 + 3 - 3[/tex]
[tex] = \bold3[/tex]